Non-communication based protection scheme using transient harmonics for multi-terminal HVDC networks. (May 2021) - Nadeem, Muhammad Haroon; Zheng, Xiaodong; Tai, Nengling; Gul, Mehr; Yu, Moduo; He, Yangyang
Highlights: A fault detection scheme is proposed for MTDC by using local transient information. Classify internal and external fault by tracking pulse count in a specific window. The concept of protection unit is employed for rapid isolation of faulty part. Results provide evidence for protection scheme's key role in handling MTDC faults. Abstract: DC faults render hindrance in the flourishment of multi-terminal flexible high voltage DC (MTDC). The fault current rises rapidly, making a sharp peak, however, under a specific fault instance, isolation of the whole network is an impractical solution. For effective reliability of the whole network, rapid and accurate fault detection and selection of faulty pole is mandatory. A fault detection scheme is proposed in this paper to draw transient current harmonics from initial fault current by utilizing Discrete Fourier transform (DFT). Current harmonics employed the fault detection promptly at the converter stations without communication among the MTDC networks. Additionally, the proposed scheme can discriminate internal from external fault by tracking the number of pulse count in a specific interval of the harmonics of the voltage. In this way, the reliability of the protection scheme enhances and escape from the mal-operation of the circuit breaker. For four terminal MTDC transmission network, the simulations are carried out in PSCAD to authenticate the implementation of the proposed scheme and protection units (PU) are utilized for the isolation of faulty part with the combination of hybrid circuit breaker (HCB). A keen analysis of test results authenticated the ability of the proposed scheme to rapidly detect the faults with high precision, along with efficient classification of the nature of faults. Furthermore, consequential results provide a strong evidence for its key role in handling a multitude of MTDC faults.